Moving house - Siegel, Mark, 1967- (New York : Roaring Brook Press, 2011)
When Joey and Chloe and their family are getting ready to move, their house decides it wants to go too.
Pub Weekly
School Library Journal
Pub Weekly, June 2011
School Library Journal, August 2011
2.4
Preschool
Keywords: Dwellings -- Juvenile fiction; Home -- Juvenile fiction; Moving, Household -- Juvenile fiction; Dwellings -- Fiction; Home -- Fiction; Moving, Household -- Fiction; Home -- Fiction; Houses -- Fiction; Moving -- Fiction; Picture books for children